Corporations in global health: an investigation of food industry political activity at the WHO. (30th September 2020) - Lauber, K; Rutter, H; McGee, D; Gilmore, A B
Abstract: Background: With over ten million annual deaths now attributable to unhealthy diets, there is an urgent need for action, yet, political progress is too slow. Policy interference by major corporations is well documented in the area of tobacco control. Evidence shows similar behaviours by the food industry at country level, but global-level policymaking remains under-researched. Thus, this study explores how food industry actors seek to influence dietary non-communicable disease (NCD) policy at the World Health Organization (WHO). Methods: We identified relevant industry documents from the Food Industry Documents Library and academic articles, using these initial findings and an existing model of corporate political activity as the basis for sixteen key informant interviews. Key industry strategies were identified in an iterative process of qualitative thematic coding. Additionally, food industry responses to five WHO consultations on NCD policy and governance (2015-2018) were analysed to explore how evidence was used. Results: Food industry actors have substantial access to the WHO through formal routes. These interactions largely take place through business associations rather than individual companies, owing at least partly to the agency's own guidelines. Food industry actors can also access global-level policymaking indirectly, for example, by lobbying national political actors to adopt favourable positions in member state-led WHO decision-making, or by co-opting civil society. In consultation responses, the majority of evidence cited by commercial actors was either industry-linked or industry-funded, and less than half was peer-reviewed. Conclusions: Focusing on the WHO's NCD agenda, we provide new insights into the ways food industry actors seek to influence global public health policy. Although their political behaviour bears similarities with that of the tobacco industry, multinational food companies are, in contrast, widely treated as part of the solution. Key messages: By mapping how food industry actors seek to shape WHO policy, this research adds to evidence from national contexts and highlights a need for better safeguards across levels of governance. While the tobacco industry is prohibited from engagement with global NCD policy, multinational food corporations enjoy significant access and legitimacy, despite similarities in political behaviour.